Mutated olfactomedin 1 in the interphotoreceptor matrix of the mouse retina causes functional deficits and vulnerability to light damage - Koch, Marcus (Histochemistry and cell biology, 2017)
Olfactomedin 1 (OLFM1) is a secreted glycoprotein and member of the olfactomedin protein family, which is preferentially expressed in various areas throughout the central nervous system. To learn about the functional properties of OLFM1 in the eye, we investigated its localization in the mouse and pig eye. In addition, we analyzed the ocular phenotype of Olfm1 mutant mice in which 52 amino acids were deleted in the central part (M2 region) of OLFM1. OLFM1 was detected in cornea, sclera, retina, and optic nerve of both wild-type and Olfm1 mutant littermates. By immunohistochemistry and double labeling with the lectin peanut agglutinin, OLFM1 was found in the interphotoreceptor matrix (IPM) of mouse and pig retina where it was directly localized to the inner segments of photoreceptors. Western blotting confirmed the presence of the OLFM1 isoforms pancortin 1 (BMY) and pancortin 2 (BMZ) in the IPM. The retinal phenotype of Olfm1 mutant mice did not obviously differ from that of wild-type littermates. In addition, outer nuclear layer (ONL) and total retinal thickness were not different, and the same was true for the area of the optic nerve in cross sections. Functional changes were observed though by electroretinography, which showed significantly lower a- and b-wave amplitudes in Olfm1 mutant mice when compared to age-matched wild-type mice. When light damage experiments were performed as an experimental paradigm of photoreceptor apoptosis, significantly more TUNEL-positive cells were observed in Olfm1 mutant mice 30 h after light exposure. One week after light exposure, the ONL was significantly thinner in Olfm1 mutant mice than in wild-type littermates indicating increased photoreceptor loss. No differences were observed when rhodopsin turnover or ERK1/2 signaling was investigated. We conclude that OLFM1 is a newly identified IPM molecule that serves an important role for photoreceptor homeostasis, which is significantly compromised in the eyes of Olfm1 mutant mice.